Múltiplas espécies e ampla polifilia no complexo Chionomesa fimbriata/lactea (Aves: Trochilidae) reveladas por análises vocais e moleculares - Coelho, Thaís Pereira Feitosa (2020)
The genus Chionomesa was recently ressurrected to group the sister species C. fimbriata and C. lactea, previously recognized as a species complex in Amazilia. Both are politypical and range in much of South America; C. fimbriata currently has seven recognized subspecies, which replace each other throughout the different tropical habitats; C. lactea has three subspecies with disjunct distributions. In view of the uncertainties about the relationship of subspecific taxa and even the validity of some of them as species, here we combined analyzes of vocal and molecular characters for the C. fimbriata and C. lactea complex, in order to assess whether the patterns of genetic divergence and similarity are associated with vocal patterns, establish the relationships of all recognized subspecies, test the validity of questionable taxa and verify if the two species are reciprocally monophyletic. For this, we compared the vocal patterns and ran multivariate analyzes (PCA and DFA) for the vocal characters, and undertook molecular analyzes on phylogeny (Maximum Likelihood and Bayesian Inference), population structure (haplotypic network) and divergence time, based on the mitochondrial marker NADH dehydrogenase subunit 2 (ND2) and the nuclear intron 7 of Beta Fibrinogen (βFib7). Part of the taxa had exclusive and diagnosable vocal patterns, but both the PCA and DFA showed overlap between some of them, including taxa belonging to different species, with the exception of C. f. tephrocephala, which segregated from all the others. The molecular data confirmed the monophyly of the genus Chionomesa, corroborating the most recent taxonomy proposed. However, the internal relationships of the subspecies showed that both C. fimbriata and C. lactea are polyphyletic, including the nominate subspecies of C. fimbriata, which was recovered as four distinct lineages. Two main clades were recovered with high bootstrap support (98.9%) and posterior probability (1): one formed by samples from western Amazonia, and the other formed by specimens from the south-central and eastern Amazonia, in addition to those from the Cerrado and eastern Brazil. The genetic divergences between the lineages ranged from 0.2% to 5.2%. In addition, haplotypes were shared between taxa subordinate to different species. The vocal analysis combined with the molecular phylogeny performed for the Chionomesa fimbriata and C. lactea complex contributes to a better understanding of the real diversity within Chionomesa, as well as the phylogenetic relationships between taxa, suggesting multiple species for this complex.